Attention Flexibility and its Relationship to Decision-Making Using the Mental Resilience and Performance (HRP) System Among the Al-Qadisiyah University Female Volleyball Team - Khamaal Mohsen Shadhan; Noor Lateef Abdul Zahre; Dunya Abdulsalam Fadhil (Pubmedia Jurnal Pendidikan Olahraga, 2026)
The current research aims to investigate the relationship between attention flexibility and decision-making using the Mental Resilience and Performance (HRP) system among female volleyball players of the Al-Qadisiyah University team. The study is based on the premise that performance in team sports relies not only on physical and technical aspects but is significantly linked to the efficiency of cognitive processes that regulate motor behavior under competitive conditions. The researcher employed a descriptive correlational approach, utilizing the HRP system tests as a standardized tool on a sample consisting of all (6) university team players. Statistical results revealed variations in attention flexibility levels (Mean: 103.7, SD: 25.1) compared to decision-making scores (Mean: 100.7, SD: 6). The findings demonstrated a strong positive correlation (0.83) at a significance level of (0.05), indicating that higher levels of attention flexibility are directly associated with improved decision-making quality during competitive situations. These results confirm that attention flexibility is a pivotal cognitive factor influencing the efficiency of tactical and technical performance. Consequently, the study recommends integrating specialized training to develop this cognitive aspect within training programs, alongside adopting scientific assessment tools to monitor mental development